Accounting information system and financial performance: Empirical evidence on Sri Lankan firms - Thennakoon, S.T.M.M.; Rajeshwaran, N. (University of Jaffna, 2022)
The research aims to examine the effect of quality of Accounting Information System (AIS) on financial performance of listed companies in Sri Lanka. Out of 290 listed companies, 165 companies were selected as a sample using Proportionate Stratified Random Sampling technique and the sample size was calculated via sample size calculator in the web using a 95% confidence level and 5% confident interval. Quality of AIS was measured through system flexibility, system sophistication, effectiveness of the system and system control as per the Contigeny Theory and Innovation Diffusion Theory. Both primary (questionnaire) and secondary (annual report) data are combined in the study. A self administrated questionnaire was issued to collect the quality of AIS, whereas the financial performances of such companies were evaluated under Return on Assets (ROA) by examining the annual reports of the selected companies. Descriptive, correlation and multiple regression analyses are applied to inspect the data. The study finds that there is a significant positive relationship between the quality of AIS and financial performance. Moreover, there is a significant impact of system flexibility, system sophistication, and effectiveness of the system towards financial performance; whilst system control also effect on financial performance, but the result is insignificant. Overall, the findings in this study are supported by other studies in the literature. The study provides a deeper understanding of how system flexibility, system sophistication, effectiveness of the system and system control of AIS quality relate to financial performance. It is recommended to maintain the highest levels of quality of AIS as it will be an advantage to raise the monetary performance of listed companies in Sri Lanka.
Keywords: AIS Quality; Financial Performance; Contigeny Theory; Innovation Diffusion Theory